Kebijakan Relokasi Warga Kampung Pulo - Rukmo, J. Endi; Amazinhono, Memorianus (Sekolah Tinggi Ilmu Pemerintahan Abdi Negara, 2015)
Relocation policy of Kampung Pulo is one program of Prevention Policy flooding in Jakarta. The flooding problem is a problem that is always faced by the provincial goverment of Jakarta on every rainy season. This issue became one of the priorities of Jokowi-Ahok when campaingning in Jakarta gubernatorial election three years ago. With the buzz and courage Governor of Jakarta was the eviction of the houses in Kampung Pulo remain to be implemented, which previously had to be disseminated to the public. Execution of the program resulted in a clash between Satpol PP with residents who cause casualities. Residents of Kampung Pulo throught mass organizations Ciliwung Merdeka preparing a lawsuit against the goverment of Jakarta to prove ownership of their land in Kampung Pulo Kampung Pulo land ownership history that began before 1930 or the Dutch colonial period Verponding basic land ownership is that the bill on the land and buildings (girik) in the Dutch colonial era. Based on the letter of citizens must convert the letter through the National Agricultural Operation Project (PRONA), since the 1960 Agarian Law to admit it. Eviction of houses is aimed at the normalization of Ciliwung. The normalization efforts started in 2013, when still a Governor Jokowi. According to the agreement the citizens want Rusunawa not far from its original home. Ahok decision was considered controversial. He is considered to be violating human rights while continuing evictions especially as the conflit and victims of the citizens, but the decisibe acation Ahok should be appreciated. Ahok do to do a Governor to address the problems in the region and in the public interest